2018
DOI: 10.1371/journal.pgen.1007390
|View full text |Cite
|
Sign up to set email alerts
|

Danger signals activate a putative innate immune system during regeneration in a filamentous fungus

Abstract: The ability to respond to injury is a biological process shared by organisms of different kingdoms that can even result in complete regeneration of a part or structure that was lost. Due to their immobility, multicellular fungi are prey to various predators and are therefore constantly exposed to mechanical damage. Nevertheless, our current knowledge of how fungi respond to injury is scarce. Here we show that activation of injury responses and hyphal regeneration in the filamentous fungus Trichoderma atrovirid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 72 publications
1
35
0
Order By: Relevance
“…Our group has previously described the early response of T. atroviride to MI (25, 26) and the role of damage-associated molecular patterns and signaling pathways (MAPKs) in the activation of the response (70). Those observations suggested that, in nature, T.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has previously described the early response of T. atroviride to MI (25, 26) and the role of damage-associated molecular patterns and signaling pathways (MAPKs) in the activation of the response (70). Those observations suggested that, in nature, T.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that when a hypha is damaged, it can regenerate, producing asexual reproduction structures (conidia) in the injured area. Later, Medina-Castellanos and coworkers (26, 70) found that the signaling pathways involved in the regulation of the response involve the mitogen-activated protein kinases (MAPKs) TMK1 and TMK3. While strains with mutations in either of the corresponding genes do not produce spores in response to injury, the production and role of metabolites in the response to mechanical injury in T.…”
Section: Introductionmentioning
confidence: 99%
“…Differential gene expression analysis was performed as described by Medina‐Castellanos et al . (2018).…”
Section: Methodsmentioning
confidence: 99%
“…ROS also play important roles in cell differentiation signalling, as discussed below (Section II.4). Extracellular ATP is another important injury‐response molecule that acts through a Ca 2+ ‐mediated cascade (Hernández‐Oñate et al ., ; Medina‐Castellanos et al ., , ). ATP in the surrounding medium is rare, and thus the presence of this molecule can be used by the fungus as a signal of cytoplasm leakage.…”
Section: Cellular Complexitymentioning
confidence: 99%